Comparing the role of social connectivity with friends and family in depression among older adults in China: evaluating the moderating effect of urban–rural status - Gu, Yuxuan; Ali, Shahmir H.; Guo, Aimei (Frontiers in Psychiatry, 2023)
Background: Social connectivity and support can reduce depressive symptoms. Few studies have examined urban-rural differences in the relationship between social support and depressive symptoms in the context of urbanization for Chinese older adults. The overall aim of this study is to examine urban-rural differences in the relationship between family support and social connectivity on depression among Chinese older adults. Methods: This cross-sectional study used data from the 2010 Sample Survey on Aged Population in Urban/Rural China (SSAPUR). Depressive symptoms were measured using the Geriatric Depression Scale short-form (GDS-15). Family support was measured by structural, instrumental, and emotional support. Social connectivity was measured using the Lubben Social Network Scale-6 (LSNS-6). Descriptive analysis was conducted using chi-square and independent t-tests to examine urban-rural differences. Adjusted multiple linear regressions were conducted to examine the moderating effect of urban-rural status on the association between types of family support and social connectivity with depressive symptoms. Results: In rural areas, respondents who felt their children exhibited filial piety (β=-1.512, p<0.001) and had more social connectivity with family (β=-0.074, p<0.001) were more likely to report fewer depression symptoms. In urban areas, respondents who received instrumental support from their children (β=-1.276, p<0.01), who thought their children exhibited filial piety (β=-0.836, p<0.01), and who had more social connectivity with friends (β=-0.040, p<0.01) were more likely to report fewer depression symptoms. In the fully adjusted regression model, social connectivity with family was associated with decreased depressive symptoms, although to a lesser degree among urban-dwelling older adults (urban-rural interaction effect, β=0.053, p<0.05). Social connectivity with friends was similarly associated with decreased depressive symptoms, although this effect was greater among urban-dwelling older adults (urban-rural interaction effect, β=-0.053, p<0.05). Conclusions: The results of this study suggested that older adults both in rural and urban areas with family support and social network were associated with fewer depression symptoms. Differences observed in the role of family and friend social connectivity by urban-rural status may provide practical information for developing targeted social support strategies for improving depressive symptoms among Chinese adults, and call for further mixed-methods research to disentangle mechanisms behind these differing associations.